Sustainability of Creative Industries: Production Dynamics in Dinoyo Ceramic Tourism Village Malang City - Sahadevi, Yoanda Alif Ya Rizqullah; Pasambe, Justin Tegar; Kamanika, GN Natta Ghiry; Poerwati, Titik; Desderius, Kevie (Badan Perencanaan Pembangunan Kota Malang, 2026)
Dinoyo Ceramic Tourism Village is an important craft center in Malang City that faces production dynamics and post-economic sustainability challenges. This research aims to analyze production patterns, constraints on the regeneration of artisans, and the role of community and institutional tourism in supporting the continuity of the ceramic business. The method used is a descriptive qualitative approach with data triangulation techniques (semistructured interviews, observations, and documentation). The results show that the local economy still relies on the production and sale of ceramics, but there is a decline in the number of active artisans, limited product diversification, and low adoption of digital marketing. The findings also indicate the potential of educational tourism and community social capital as assets, but the realization of its benefits is hampered by weak human resource regeneration and uncoordinated institutional support. The analysis confirms that the sustainability of the center is largely determined by the synergy of three factors: product innovation and marketing, skills regeneration programs, and local institutional/political interventions. This article recommends integrated interventions in the form of digital design and marketing training, apprenticeship programs for the younger generation, and strengthening community-government collaboration for sustainable revitalization. This study contributes to the development of creative industry sustainability by integrating production dynamics, innovation capacity, and institutional support within a tourism village context.